Digitalization, crowdfunding, eco-innovation and financial development for sustainability transitions and sustainable competitiveness: Insights from complexity theory - Amal Dabbous; Karine Aoun Barakat; Abbas Tarhini (Journal of Innovation & Knowledge (JIK), 2024)
The introduction of digitalization and the promotion of eco-innovation, the move towards financial development, and the appearance of alternative financial practices such as crowdfunding as well as the adoption of freer economic systems represent plausible enablers of the sustainable transition and potentially help to increase nations' sustainable competitiveness. However, knowledge is scarce about their contribution. The present study fills the gap in the sustainability literature by proposing a complexity theory lens to a dataset spanning four years from 2015 to 2018 for 18 countries which captures the possible configurations of the chosen factors that allow countries to achieve two outcomes: sustainability transitions and sustainable competitiveness. The findings show three configurations for each outcome. High levels of digitalization, crowdfunding, and financial development are present in all configurations showing their important contribution to sustainable competitiveness and sustainability transitions. High eco-innovation and economic freedom are present in four out of six solutions, while they are present in negation (low levels) in the remaining two solutions. Overall the results offer insights to policymakers, individuals, and businesses on how to use these findings to understand the complex interactions generating high sustainability transitions and sustainable competitiveness.
Keywords: O00; Q01; Q55; G20; 650; Transitions to sustainability; Sustainable competitiveness; Digitalization; Crowdfunding; Eco-innovation; Financial development; fsQCA